Pengaruh Model Pembelajaran Group Investigation terhadap Hasil Belajar pada Mata Pelajaran Geografi - Rini Indri Safitri; I Putu Ananda Citra (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to (1) examine the implementation of the audiovisual-based Group Investigation learning model in Geography subjects, and (2) analyze the effects of the audiovisual-based Group Investigation model on students' learning outcomes in Geography at SMA Negeri 5 Denpasar. This research employs a quasi-experimental method with a Non-equivalent Control Group Design. The study involves two classes: (1) Class X.2 (experimental class) which received the audiovisual-based Group Investigation learning model, and (2) Class X.1 (control class) which used the conventional learning model. Data were collected using observation instruments and students' learning outcome tests, and were analyzed using Liliefors, Levene's, and t-tests. The results of the study indicate that:(1) The implementation of the audiovisual-based Group Investigation learning model significantly improved students' learning outcomes, as evidenced by the comparison of results between the control and experimental classes,(2) The audiovisual-based Group Investigation model implemented by teachers at SMA Negeri 5 Denpasar proved to have a significant impact on students' learning outcomes. The experimental class showed a significant improvement in learning outcomes compared to the control class. The findings of this study demonstrate a significant enhancement in the learning outcomes of students in the experimental class. Therefore, the audiovisual-based Group Investigation learning model is effective in improving students' learning outcomes.